Chemical compositions of Antarctic meteorites I - Haramura, Hiroshi; Kushiro, Ikuo; Yanai, Keizo (1983)
P(論文) Sixty-four chondrites (14H, 25L, 17LL and 8C), 32 achondrites and 2 rare stony-iron meteorites from Antarctica were analyzed by standard wet chemical analysis method. In the present paper the analyses of the chondrites and the stony-iron meteorites are reported. Many Antarctic meteorites are more or less weathered or oxidized. Analyses of fresh and weathered parts of three chondrites indicate that abundances of most major elements are essentially the same between the two parts except for the proportions of Fe, FeO and Fe_2O_3. The analyses of the chondrites show that H chondrites and L and LL chondrites are distinct in several components (e. g., Na_2O is separated at 0.85wt%). When iron and FeS are subtracted, however, all the ordinary chondrites have essentially the same compositions, although H chondrites are slightly higher in Mg and lower in Si than L and LL chondrites. The compositions of the eight carbonaceous chondrites indicate that they comprise both C2 and C3 types in equal number. The analyzed carbonaceous chondrites are distinctly lower in SiO_2,Na_2O and K_2O and higher in MgO, Al_2O_3 and CaO than the ordinary chondrites. The stony-iron meteorites analyzed are similar to lodranite; however, one differs from lodranite in SiO_2,Al_2O_3 and CaO, and the other differs in SiO_2 and Fe/Mg ratio. departmental bulletin paper